Sustaining Agriculture through Climate Change (SACC): CARE International - Shames, Seth; Onyango, G. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Case study for the report "Institutional innovations in African smallholder carbon projects" available at http://hdl.handle.net/10568/21222